STRATEGIES FOR DEVELOPING PALM OIL MARKETING CHANNELS: A LITERATURE REVIEW ON PROFIT MARGINS, FARMER SHARES, AND DISTRIBUTION CHAIN OPTIMISATION - Afwan Sila; Ari jumadi Kirnadi; Adi Mursalin (Adisam Publisher, 2025)
This study aims to analyse strategies for developing palm oil commodity marketing channels through a literature review approach that highlights aspects of profit margins, farmers' share, and distribution chain optimisation. This study was motivated by the issue of uneven distribution of added value between farmers and industry players, as well as logistical inefficiencies in the palm oil marketing system in Indonesia. The results of the analysis show that the uneven profit margins and low farmer's share are mainly caused by the length of the distribution chain, weak farmer institutions, and limited access to market information. Distribution chain optimisation can be achieved through the application of digital technology, price transparency, and institutional integration between farmers, cooperatives, and the processing industry. Digitalisation, strategic partnerships, and logistics policy reforms are key strategies for creating an efficient, inclusive, and sustainable marketing system. This study recommends the development of a technology-based and sustainable collaborative marketing model as the basis for policies to improve the competitiveness and welfare of palm oil farmers at the national level.